Pengaruh Metode QuantuMaky terhadap Percepatan Menghafal Al-Qur’an Santri di Rumah Tahfiz Mafaza Tangerang - Sandriana, Fifi; Putra, Rido (Lembaga Yasin AlSys, 2025)
The limited number of studies on the effectiveness of innovative methods for accelerating Qur’anic memorization underlies this research, despite the phenomenon's significant implications for the quality of tahfiz education in the digital era. This study aims to analyze the effect of the QuantuMaky method on the acceleration of Qur’anic memorization among students at Rumah Tahfiz Mafaza Tangerang. Employing a quantitative approach with a survey method, the study involved 82 respondents determined using Slovin’s formula from a population of 450 students. The primary instrument was a Likert-scale questionnaire, and data were analyzed using simple linear regression. The results show a coefficient of determination (R²) of 0.476, indicating that 47.6% of memorization acceleration is influenced by the application of the QuantuMaky method. The t-test yielded a calculated t value (8.517) greater than the critical value (1.664) at a significance level of < 0.05, confirming a positive and significant effect of the QuantuMaky method on memorization speed. The study concludes that the QuantuMaky method is effective in enhancing the quality and speed of Qur’anic memorization. The implications of these findings include a theoretical contribution to the literature on modern tahfiz methods and practical recommendations for Islamic educational institutions to integrate this method into their curricula. This study also opens avenues for further exploration into long-term retention and the psychological aspects of memorization among students.